Interventions for tobacco cessation delivered by dental professionals - Holliday, R; Hong, B; McColl, E; Livingstone-Banks, J; Preshaw, PM (Cochrane Collaboration, 2021)
Background Dental professionals are well placed to help their patients stop using tobacco products. Large proportions of the population visit the dentist regularly. In addition, the adverse effects of tobacco use on oral health provide a context that dental professionals can use to motivate a quit attempt.